The Association Between Body Mass Index (BMI) and Occupation with the Incidence of Hemorrhoids at Mitra Sejati General Hospital, Medan, in 2023 - Horas Rejeki Manik; Elizabeth Septianur Girsang; Alexander Parlindungan Marpaung; Suryati Sinurat; Harry Butarbuta (Jurnal Kedokteran Methodist, 2025)
Background: Hemorrhoids are a very commonanorectal condition defined as symptoms ofenlargement and displacement of the normal anal padto distal. The causes of hemorrhoids themselves arestill idiopathic or not widely known, but many arecaused by age, gender, lack of drinking and fiberconsumption, constipation, occupation, genetics, lackof exercise, overweight, increased intraabdominalpressure. Objective: This study aimed to determinethe relationship between body mass index andoccupation in hemorrhoid incidence. Methods: Thistype of study uses an observational analyticalmethod, with a crosssectional design, a datacollection method using secondary data obtainedfrom medical records diagnosed with hemorrhoids atMitra Sejati Hospital, Medan city in 2023. Results:The results of this study showed that there was arelationship between body mass index and theincidence of hemorrhoids with a value of p = 0.024,and there was a significant relationship between workand hemorrhoids with a value of p = 0.031.Conclusion: There is a relationship between bodymass index and occupation in hemorrhoid incidenceKeywords: hemorrhoids, body mass index,occupationz